Impact of the COVID-19 pandemic on digital communication among secondary mathematics students - N, Mohamed-Chemlali; H, Hossein-Mohand; H, Hossein-Mohand; S, Osuna-Acedo (Journal of Education and e-Learning Research, 2025)
The study examines the impact of the COVID-19 pandemic on mathematical communication among secondary education students focusing on digital interactions with peers and teachers, using social networks for educational purposes, and the utilization of technological devices for studying mathematics. A non-experimental, quantitative, ex post facto research design was employed, analyzing data from 2728 secondary school students in Melilla, Spain. Data were collected through a structured questionnaire administered in 2019 and 2024 measuring variables related to digital communication, social network usage, and device-based learning. Statistical analyses were performed using generalized linear models to evaluate the significance of observed trends. Results reveal a significant increase in peer communication and the use of social networks for sharing educational resources. Teacher-student communication also increased though the improvement was moderate and uneven across educational levels. The use of technological devices for learning mathematics at home grew notably among lower secondary students but less so in upper secondary. Findings underscore the transformative role of digital platforms in fostering academic interaction during the pandemic and highlight persistent challenges including teacher preparedness and equitable access to technology. The results highlight the need for targeted policies to strengthen digital competencies and bridge the digital divide in education.